Metabolic tracing analysis reveals substrate‐specific metabolic deficits in platelet storage lesion. Issue 11 (23rd August 2017) - Sims, Carrie; Salliant, Noelle; Worth, Andrew J.; Parry, Robert; Mesaros, Clementina; Blair, Ian A.; Snyder, Nathaniel W.
Abstract : BACKGROUND: Storage of platelets (PLTs) results in a progressive defect termed PLT storage lesion (PSL). The PSL is characterized by poor PLT quality on a variety of assays. Metabolic defects are thought to underlie the PSL; thus this study was designed to quantitatively probe specific metabolic pathways over PLT storage. STUDY DESIGN AND METHODS: Relative incorporation of stable isotope‐labeled substrates was quantified by isotopologue analysis of key acyl‐coenzyme A (CoA) thioester products for fresh, viable (after collection, Days 2‐5), and expired PLTs (after Day 5). We examined the incorporation of acetate, glucose, and palmitate into acetyl‐ and succinyl‐CoA via liquid chromatography–tandem mass spectrometry. RESULTS: Storage‐related defects in the incorporation of acetyl‐CoA derived from acetate and palmitate were observed. Carbon derived from palmitate and acetate in succinyl‐CoA was reduced over storage time. Glucose incorporation into succinyl‐CoA increased in viable PLTs and then decreased in expired PLTs. Carbon derived from octanoate and pyruvate remained partially able to incorporate into acetyl‐ and succinyl‐CoA in expired PLTs, with high variability in pyruvate incorporation. CONCLUSION: Isotopologue analysis is useful in probing substrate specific defects in the PSL.